Why Wittgenstein Fled Vienna with His (Wittgenstein’s) Ahistoricity in His Suitcase - Distaso, Leonardo V. (Scenari, 2022)
The personal and intellectual relationship that Wittgenstein had with Austrian culture was contradictory. On the one hand, he was a product of Viennese culture and life; on the other, he fled from Vienna and Austria to take new and culturally different paths. This essay tries to highlight these contradictions.